Knowledge of Traditional Birth Attendants in the Provision of Safe Delivery Care According to Health Standards Evidence from Longsheng Village, Rural China - Xia, Jianfu; Wu, Junjie; Lo, Victor Ei-Wen; Tseveen, Erkhembayar; Nazilovna, Zhumagaliyeva Ardak (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: This study aimed to assess the level of knowledge of traditional birth attendants as community-based health providers in delivering safe childbirth care according to health standards in Longsheng Village, a rural ethnic minority area in China.Methodology: A community-based cross-sectional analytical study was conducted involving all active traditional birth attendants in Longsheng Village (n = 32). Data were collected using a structured and validated knowledge questionnaire developed based on WHO safe motherhood and essential obstetric care guidelines. The instrument assessed four competency domains: recognition of pregnancy danger signs, safe delivery procedures, infection prevention, and referral systems. Descriptive statistics were used to summarize knowledge levels, and a one-sample t-test was applied to compare the mean knowledge score with a predefined competency benchmark of 80%. Instrument reliability was confirmed with a Cronbach’s alpha coefficient of 0.87.Main Findings: The findings showed that only 7 respondents (21.8%) demonstrated adequate knowledge of safe delivery care, while the majority (78.2%) had low to moderate knowledge levels. The overall mean knowledge score was significantly lower than the competency benchmark (p < 0.001). The lowest scores were observed in the domains of referral procedures and infection prevention, indicating critical gaps in emergency response readiness and clinical safety awareness.Novelty/Originality of this study:  These findings highlight an urgent need for competency-based training, strengthened referral systems, and closer integration between TBAs and formal health services to improve maternal and neonatal safety in rural ethnic minority settings.